The implications of varicose vein surgery on sleep evaluation scales - Acir, Ibrahim; Okudan Atay, Zeynep Vildan; Atay, Mehmet; Yayla, Vildan (Frontiers in Psychiatry, 2023)
Background Varicose veins commonly occur on the legs and cause discomfort, pain, and aesthetic issues. Varicose vein surgery has an significant impact on sleep disorders such as Restless Leg Syndrome (RLS), daytime sleepiness (DS), and sleep quality (SQ). We intended to determine if preoperative and postoperative sleep quality, excessive daytime sleepiness, and RLS severity impacted in those who had varicose vein surgery. Materials and methods The research included 160 patients who presented to the Cardiovascular Surgery outpatient clinic with symptoms of leg pain and cramping and were diagnosed with venous insufficiency. The Restless Legs Syndrome Study Group Rating Scale (RLSS), Epworth Sleepiness Scale (ESS), and Pittsburgh Sleep Quality Index (PSQI) tests were performed on patients. The patients’ scores on the scales were compared preoperatively and postoperatively. Results The mean age of the 160 patients was calculated to be 48.7 ± 10.6 years. There were 109 female (68.1%) and 51 male (31.9%). The mean ferritin level of the patients was calculated as 61.4 mL/ng (4.3–421 mL/ng). After varicose vein surgery 63% reported improved sleep quality. Individuals with increased DS had lower postoperative RLSS scores and higher SQ. There was a decrease in postoperative RLSS scores and an increase in postoperative SQ in patients with normal DS (p < 0.001). Postoperative RLSS and DS scores were lower in patients with good SQ (p < 0.001). Conclusion Patients had a lower RLSS score, a lower DS score, and a higher SQ after varicose vein surgery. Surgical treatment is critical to improving the quality of life and sleep comfort of patients with varicose veins and sleep disorders.